The Eyre Affair de Jasper Fforde : une expérience de critique amusante - Yen-Maï Tran-Gervat (Revue LISA)
In his intertextual and metatextual novel, J. Fforde does not propose a specific, coherent interpretation of Jane Eyre: his parody is more an “amusing critical experiment”, a playful narrative in which Charlotte Brontë’s romance is brought to life in a way that allows every reader to deal with such critical issues in Jane Eyre as point of view, the controversial ending and the creation of characters.